Manifesto of the Epicurean Philosophy of Life - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2019)
Epicurus’ philosophy grew out of his life experiences, contacts, polemics, journeys and other activities. Apart from such great works as the monumental On nature (Peri phuseôs) in 37 books, Epicurus authored also various extracts (epitomai), principle doctrines, sayings and letters. The letters, while addressed to many students and friends, were for him a very important tool of propagating his own philosophy. Epicurus’ fascinating Letter to Menoeceus can be regarded as a manifesto of his philosophy of life. In historiography, it is often characterized as an exposition of his ethics, even though Epicurus probably did not use the term himself. To better capture the composition and spirit of this work, the Greek text of the letter has been somewhat rearranged here: for the sake of clarity, ample spaces and special paragraphs have been provided, and appropriate headings have been introduced in the Polish translation.